Vector-Borne Bacterial Plant Pathogens: Interactions with Hemipteran Insects and Plants - Perilla-Henao, Laura M.; Casteel, Clare L. (Frontiers in Plant Science, 2016)
Hemipteran insects are devastating pests of crops due to their wide host range, rapid reproduction, and ability to transmit numerous plant-infecting pathogens as vectors. While the field of plant-virus-vector interactions has flourished in recent years, plant-bacteria-vector interactions remain poorly understood. Leafhoppers and psyllids are by far the most important vectors of bacterial pathogens, yet there are still significant gaps in our understanding of their feeding behavior, salivary secretions, and plant responses as compared to important viral vectors, such as whiteflies and aphids. Even with an incomplete understanding of plant-bacteria-vector interactions, some common themes have emerged: 1) all known vector-borne bacteria share the ability to propagate in the plant and insect host; 2) particular hemipteran families appear to be incapable of transmitting vector-borne bacteria; 3) all known vector-borne bacteria have highly reduced genomes and coding capacity, resulting in host-dependence; and 4) vector-borne bacteria encode proteins that are essential for colonization of specific hosts, though only a few types of proteins have been investigated. Here, we review the current knowledge on important vector-borne bacterial pathogens, including Xylella fastidiosa, Spiroplasma spp., Liberibacter spp., and 'Candidatus Phytoplasma spp.’. We then highlight recent approaches used in the study of vector-borne bacteria. Finally, we discuss the application of this knowledge for control and future directions that will need to be addressed in the field of vector-plant-bacteria interactions.